AI-Integrated Science Teaching Through Facilitating Epistemic Discourse in the Classroom - Kim, Won Jung (Asia-Pacific Science Education, 2022)
Abstract We have entered the Fourth Industrial Revolution, which has brought widespread digital transformation with advanced and broadened technologies including artificial intelligence (AI). To help students prosper in a world full of AI applications, it is important for us to offer students sufficient AI-integrated learning opportunities across different subjects, including science. In this position paper, a pedagogical approach to AI-integrated science education through facilitating epistemic discourse is proposed. To establish a foundation for this integration, epistemic similarities and differences between how scientific knowledge is constructed and how AI agents learn are compared, referring to Chinn et al.'s (2014) epistemic cognition framework that attends to epistemic aims, ideals, and processes. Four bins of instructional strategies for facilitating epistemic discourse in AI-integrated science classrooms is suggested, which will help students more readily act as informed knowledge constructors, critics, and users of AI and science, who can pose questions that matter to their lives.